Understanding pupils' hiding techniques in physical education. Issue 8 (16th November 2016) - Lyngstad, Idar; Hagen, Per-Magnus; Aune, Ola
Abstract : Previous research shows that some pupils find physical education (PE) demanding and difficult. Some pupils use strategies to avoid participation in PE when it is demanding and difficult. The present study aims to illuminate and describe strategies used by pupils to avoid negative self-perception in difficult situations and activities in PE classes. This behavior, called hiding techniques, arises out of the need to protect self-perception and save academic or social face in the PE subject. Interviews and focus groups have been used with six PE teachers in Norwegian primary and lower secondary school to illuminate hiding techniques. Ten former pupils have also been interviewed about their experience of PE classes in primary/lower secondary school and upper secondary school for the same purpose. The results show that hiding techniques are experienced and practised in many different ways, and that there is a wide range of causes behind hiding techniques. Pupils' hiding techniques are categorized into main types, and the causes underlying the hiding techniques are summarized. This study provides insight into educational challenges that need to be highlighted to help all pupils in school, not just those who complete the PE subject without any real problems, to realize an important aim of the subject and to experience the joy of movement and lasting physical activity. It also highlights hiding techniques that are sophisticated, clever and deliberate actions pupils use to take control over the social setting in PE through the covert act of resistance rather than passively allowing the oppressive social setting to overpower them.